Correction of broadband snow albedo measurements affected by unknown slope and sensor tilts - Weiser, Ursula; Olefs, Marc; Schöner, Wolfgang; Weyss, Gernot; Hynek, Bernhard (The Cryosphere, 2016)
Geometric effects induced by the underlying terrain slope or by tilt errors of the radiation sensors lead to an erroneous measurement of snow or ice albedo. Consequently, artificial diurnal albedo variations in the order of 1–20 % are observed. The present paper proposes a general method to correct tilt errors of albedo measurements in cases where tilts of both the sensors and the slopes are not accurately measured or known. We demonstrate that atmospheric parameters for this correction model can either be taken from a nearby well-maintained and horizontally levelled measurement of global radiation or alternatively from a solar radiation model. In a next step the model is fitted to the measured data to determine tilts and directions of sensors and the underlying terrain slope. This then allows us to correct the measured albedo, the radiative balance and the energy balance. Depending on the direction of the slope and the sensors a comparison between measured and corrected albedo values reveals obvious over- or underestimations of albedo. It is also demonstrated that differences between measured and corrected albedo are generally highest for large solar zenith angles.